A DEEP LEARNING-BASED TECHNIQUE FOR MEASURING THE SUCCESS OF ORTHODONTIC TREATMENT - Zahraa Jabbar , Qabas Abdal; Ali Hashim, Firas; Thanoon Ahmed, Nada; Mahmood Hussien, Nadia; Makki Mohialden, Yasmin; Saad Mohammed, Itidal (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2023)
Orthodontics is one of the most advanced procedures for achieving long-term stability with functional and aesthetically pleasing results. This study aims to evaluate the effectiveness of orthodontics by measuring the distances between each pair of teeth using k-means algorithm utilities from deep learning. The system creates Python-based tools, such as Numpy and OpenCV, from an integrated package. This instrument can assist the dentist in making decisions regarding gum disease, dental impaction, excessive teeth, tooth loss, and orthodontics. Because making an informed decision on an extraction pattern is crucial to the success of orthodontic treatment and the stability of long-term outcomes.